BIAYA PENDIDIKAN SEBAGAI PEMODERASI PENGARUH MOTIVASI KARIR DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA AKUNTANSI MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Suyasa, Krisnadi Wira; Widanaputra, Anak Agung (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
Accounting Profession Education (PPAk) is a type of higher education after the degree program established to produce professional accountants. This study aims to determine the effect of career motivation and economic motivation on the interests of accounting students follow Accounting Profession Education and how the cost of education can affect the relationship motivation and career motivation of the economic interests of accounting students follow Professional Accounting Education. This research was conducted at the Faculty of Economics and Business Udayana University by using questionnaire technique as the method of data collection. Total population of 79 students of non-regular program accounting class of 2013 and 2014 by using method of determining purposive sampling samples. The analysis technique used is moderated regression analysis (MRA). Based on the results of research conducted it is known that the higher the motivation of career then the higher interest of accounting students follow Accounting Profession Education, especially if the cost is low. The higher the motivation of career then the higher interest of accounting students follow Accounting Profession Education, without being influenced by the cost of education.